PCB cushion and preparation process
Patent Information
- Application Number
- CN202611299049.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-16
AI Technical Summary
[0008]为了解决现有缓冲垫背面结合力弱、正面介电性能受烧结影响、厚度一致性差的痛点,本申请的目的之一在于提供一种PCB缓冲垫,能够兼顾正面低介电、背面高结合力且整体厚度稳定的特点
(1)正面性能稳定:两次PI涂覆+350℃封顶脱蜡,既保证正面碳纳米管分散均匀、介电性能优异,又避免高温烧结破坏PI分子结构,正面耐磨性提升40%以上。
Smart Images

Figure CN122934634A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of PCB lamination consumable manufacturing technology, specifically to a PCB buffer pad and its preparation process. Background Technology
[0002] Currently, existing PCB lamination buffer pads have the following problems during manufacturing: 1. The front side is easily worn: Conventional buffer pads mostly use a single-coat pure polyimide (PI) process on the front side, which is prone to pinholes and bubbles. The dielectric constant Dk is generally ≥3.0, which cannot meet the requirement of Dk≤2.5 for high-frequency boards. The multi-walled carbon nanotubes added to improve thermal conductivity have poor dispersibility. When the amount added exceeds 0.05wt%, they will agglomerate. After 10 to 20 pressing cycles, powder will fall off the front side, which not only contaminates the board surface, but also reduces the yield by more than 15%.
[0003] 2. Weak Back-End Adhesion: Conventional cushioning pads only have a roughened finish on the back or are directly coated with unsintered PTFE raw adhesive. When only roughened, the raw adhesive merely physically adheres to the base fabric surface. After 3-5 presses, the raw adhesive peels off, the base fabric frays, resulting in indentations and delamination on the PCB board surface. If PTFE is directly applied without sintering, the interlayer adhesion is weak; if the entire layer is sintered, it will damage the dielectric properties of the polyimide on the front side.
[0004] 3. Poor thickness consistency: Conventional buffer pads often use a thick layer of PTFE to improve bonding strength, resulting in a thickness increase of ≥0.05mm after lamination. This far exceeds the requirement of ≤±0.02mm for buffer pad thickness tolerance in high-frequency and high-speed boards, which can easily lead to uneven thickness of the lamination medium. The Cpk value is only about 1.0, which cannot meet the requirements of high-end boards.
[0005] 4. High risk of steel plate damage: The front PI surface of conventional buffer pads has poor wear resistance. When directly attaching and pressing the steel plate, it is easy to scratch the mirror surface of the steel plate (roughness Ra≤0.4μm), or cause the steel plate to be scrapped. If an excessively thick release layer is added, the thickness of the stack will be further increased, exacerbating the loss of medium thickness control.
[0006] 5. Short lifespan and high cost: Conventional kraft paper cushioning pads have a lifespan of only 30 to 50 cycles, while imported PCM high-performance pads have high unit prices and long delivery times. Furthermore, neither of them has a thickness lifespan management mechanism, which can easily lead to mass scrapping due to overuse.
[0007] Therefore, in order to solve the problems of weak back adhesion, sintering-affected front dielectric properties, and poor thickness consistency of existing buffer pads, it is urgent to develop a PCB buffer pad and its manufacturing process that can balance low front dielectric, high back adhesion, and stable overall thickness. Summary of the Invention
[0008] To address the shortcomings of existing buffer pads, such as weak back adhesion, front dielectric properties affected by sintering, and poor thickness consistency, one of the objectives of this application is to provide a PCB buffer pad that can balance the characteristics of low front dielectric, high back adhesion, and stable overall thickness.
[0009] The second objective of this application is to provide a manufacturing process for a PCB buffer pad, in which the pad achieves surface contact and clamping with the steel plate through pressing pressure, without the need for adhesive or mechanical connection.
[0010] To address the aforementioned technical problems, one of the objectives of this application is achieved through the following technical solution: A PCB cushioning pad includes a base fabric layer, a PI layer and a PTFE transition layer respectively disposed on the front and back sides of the base fabric layer, and a composite backing layer disposed outside the PTFE transition layer. The back side of the base fabric layer has a micro-anchoring structure, and the PTFE transition layer fills the micro-anchoring structure and is anchored to the base fabric layer.
[0011] The PCB cushioning pad consists of a base fabric layer, a front PI layer, a back PTFE transition layer, and a composite back layer. The front side uses PI (polyimide) to ensure low dielectric strength and abrasion resistance, while the back side uses PTFE+FEP to ensure adhesion and cushioning, achieving a synergistic effect of one side being hard (abrasion-resistant / low dielectric) and the other soft (high adhesion / cushioning). In particular, the back side features a micro-anchoring structure, with the PTFE transition layer filling it to form an anchoring connection. This overcomes the limitations of traditional cushioning pads that rely solely on physical pressing or simple coating. The "micro-anchoring structure" achieves mechanical interlocking between PTFE and the base fabric, significantly improving interlayer bonding and solving the problem of weak back adhesion and adhesive detachment after 3-5 pressing cycles in existing PCB cushioning pads.
[0012] Preferably, the thermally conductive filler is a single-arm carbon nanotube, and the amount added is 0.07~0.09% of the weight of the PI layer.
[0013] The thermally conductive filler is single-arm carbon nanotubes (SWCNTs), added at a concentration of 0.05%~0.1%. SWCNTs possess an extremely high aspect ratio, enabling the formation of an effective thermal / electrical conductive network even at very low addition levels (0.05%~0.1%). Compared to multi-walled nanotubes, this method increases thermal conductivity by 30% at the same addition level, while avoiding the decline in mechanical properties caused by agglomeration. This solves the problems of easy agglomeration and high addition amounts associated with multi-walled carbon nanotubes in existing technologies.
[0014] Preferably, the composite backing layer is formed by curing a mixture of PTFE raw rubber and FEP, and the mass percentage of FEP in the composite backing layer is 15% to 25%.
[0015] Pure PTFE raw rubber has generally poor adhesion, while pure FEP has a low melting point but is expensive and has different performance characteristics. Introducing 15%~25% FEP improves the interlayer adhesion between the composite backing layer and the base fabric layer. Simultaneously, combined with the non-sintering characteristic of PTFE raw rubber, it controls the thickness increase (≤0.02mm), solving the industry problem of poor thickness uniformity. Through combination with a micro-anchoring structure, the mixture can penetrate into the microporous anchoring pit without additional thickness buildup, resulting in a total thickness of only 0.36mm (the industry standard thickness for PCM pads), a thickness tolerance of ±0.01mm, and a thickness uniformity Cpk ≥1.67. Combined with a PTFE transition layer, it solves the problems of weak backing adhesion, large thickness increase, and poor interlayer adhesion.
[0016] The second objective of this application is achieved through the following technical solution: A process for manufacturing a PCB buffer pad, the process steps including: S1. Front PI layer coating: On a horizontal coating machine, a polyimide emulsion containing thermally conductive filler is scraped onto the front side of the dewaxed and split base fabric to avoid pinholes caused by a single thick coating and to ensure the abrasion resistance and low dielectric consistency of the front side. S2, Vertical Step Dewaxing: The coated base fabric is transferred into a vertical oven and dewaxed by stepping up the temperature from 150℃ to 200℃ to 280℃ to 350℃. Throughout the process, the coating surface is kept from sticking to the top roller to protect the carbon nanotube conductive network on the front side and ensure the dimensional stability of the base fabric. S3. Reverse treatment: The reverse side of the base fabric is roughened with a 200# diamond roller to form uniformly distributed micro-anchoring pits without cutting the warp and weft yarns of the EW354 base fabric, thus preserving the tensile strength of the base fabric itself. S4. PTFE coating and sintering on the reverse side: PTFE emulsion is coated on the reverse side of the base fabric after surface roughening treatment, followed by short-time high-temperature sintering at 350℃, so that PTFE melts and fills the micro-anchoring pits. After cooling, a dense sintered PTFE transition layer is formed, which not only forms a strong chemical bond with the base fabric, but also provides a smooth and compatible bonding interface for the subsequent drip layer. Step S5, Reverse Mixed Emulsion Dropping: The mixed emulsion of PTFE raw rubber and FEP is dropped onto the surface of the sintered PTFE transition layer. Relying on capillary action and surface tension, it penetrates into the remaining micropores of the transition layer, so that the raw rubber forms a film but does not sinter. Then, it is dried at a low temperature of 280℃ to form the composite back side.
[0017] This method employs an asymmetric process of "front-side treatment followed by reverse-side anchoring." The front PI layer is sintered through a scraping process to form a dense "glaze" with a friction coefficient ≤0.15, exhibiting excellent wear resistance. It will not scratch or stick when directly contacting the mirror surface of the steel plate, reducing the cost of the release layer. Simultaneously, the PI surface has better thermal conductivity than the PTFE surface, improving heat distribution. The reverse side is first coated with PTFE emulsion, and the sintered PTFE melts and fills 90% of the micro-anchoring pits, forming a strong chemical bond with the base fabric. This enables a back-side peel strength of 12.3 N / cm (compared to the conventional 5~8 N / cm). The composite backing is cured by drip-casting and scraping with a mixed emulsion of PTFE raw rubber and FEP without sintering, allowing the mixture to penetrate the micropores without additional buildup. The total thickness is only 0.36mm (the industry standard thickness for PCM pads), with a thickness tolerance of ±0.01mm and a thickness uniformity Cpk ≥1.67. 20% FEP enhances interlayer adhesion, preventing slippage and wrinkling during pressing, reducing the wrinkling rate in open areas from 49.44% to 0%. This solves the problems of large thickness increase and poor interlayer adhesion leading to uncontrolled thickness in traditional scraping processes. In particular, the drip-casting method utilizes capillary action to penetrate into the micro-anchoring pits, ensuring bonding strength while achieving zero or extremely low thickness increase. It is compatible with the industry-standard thickness of 0.3~0.5mm for PCB lamination buffer pads, which can fill the 5~10μm micro-unevenness between the steel plate and the workpiece without increasing the total thickness of the stack. When used with steel plates, there is no need to adjust the original lamination program parameters.
[0018] Preferably, the emulsion in step S1 is an oily polyimide emulsion containing 0.07~0.09 wt% single-arm carbon nanotubes, wherein the single-arm carbon nanotubes are 301 type single-arm carbon nanotubes, which are dispersed and added to the oily polyimide emulsion in two stages, and the total thickness of the two coatings is 25~35 μm.
[0019] The front PI layer uses an oil-based polyimide emulsion containing 0.07~0.09wt% single-arm carbon nanotubes. This oil-based polyimide emulsion containing single-arm carbon nanotubes is applied in two coats to the front of the dewaxed and split base fabric using a horizontal coating method. This solves the problems of pinholes, bubbles, and uneven thickness on the front side, avoiding defects from a single thick coating. Combined with 350℃ stepped dewaxing, the thermal conductivity of the front PI layer is increased by 30%, density by 35%, and abrasion resistance by 40% at the same additive content. Even after 500 pressing cycles, there is no powder shedding, allowing direct contact with the steel plate without damaging the mirror surface. This solves the problems of poor thermal conductivity, high dielectric constant, and easy agglomeration of the front PI layer in existing PCB buffer pads. In particular, 0.08wt% is the optimal critical point: below this value, an effective thermal conductive network cannot be formed; above this value, agglomeration easily degrades mechanical properties.
[0020] Preferably, in step S3, a 200# diamond roller is used for surface roughening treatment, with a roughening depth of 15~20μm and an anchoring pit density of ≥200 pits / mm². This can form sufficient anchoring force without cutting the warp and weft yarns of the base fabric, thus preserving the strength of the base fabric itself.
[0021] Preferably, the sintering temperature in step S4 is 350°C, the time is 6 minutes, and the front surface temperature is ≤350°C.
[0022] Preferably, the sintering in step S4 is a partial back-side treatment, and the heat has been reduced to below 350°C by the time it is conducted to the front side, so as not to affect the performance of the front PI layer.
[0023] PTFE sintering typically requires high temperatures (350℃+), but prolonged high temperatures may degrade the PI layer or impair its dielectric properties. Therefore, the sintering temperature is 350℃ for 6 minutes; the front-side temperature is ≤350℃. Simultaneously, through localized treatment, heat conduction is controlled to ensure that the PTFE on the back side fully melts and fills the anchoring pits, while the heat conducted to the front side is reduced, thus not affecting the PI performance on the front side and resolving the conflict between material temperature resistance.
[0024] Preferably, the PTFE emulsion in step S4 has a solid content of 60%, a wet film thickness of 10-20 μm after coating, and a dry film thickness of 5-10 μm after sintering.
[0025] This thick sintered PTFE layer is not just a binder, but also a transition layer. It fills 90% of the roughening pits, providing a smooth interface for the subsequent drip layer and preventing the drip fluid from over-penetrating and causing insufficient adhesive.
[0026] Preferably, in step S5, the solid content of the PTFE raw rubber and FEP mixed emulsion is 18%~22%, the dripping amount is 20~40g / m², the drying temperature is 280℃, the raw rubber forms a film but does not sinter, and the thickness increase on the back side after lamination is ≤0.02mm.
[0027] Sintering PTFE raw rubber leads to shrinkage, hardening, and loss of cushioning properties. Therefore, controlling the drying temperature at 280℃ helps maintain the raw rubber's flexibility and adhesion, while FEP is used to assist in film formation. The addition rate is 20~40 g / m², combined with an infiltration process, ensuring that the back-side thickness increase after lamination is ≤0.02 mm, meeting the stringent thickness tolerance requirements of high-frequency boards (Cpk≥1.67). Especially when the FEP content is around 20%, it improves interlayer adhesion, eliminates slippage and wrinkling during lamination, and reduces the wrinkling rate in open areas from 49.44% to 0%.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Stable front-side performance: Two PI coatings + 350℃ capping and dewaxing ensure that the carbon nanotubes on the front side are evenly dispersed and have excellent dielectric properties, while avoiding high-temperature sintering that damages the PI molecular structure, thus improving the wear resistance of the front side by more than 40%.
[0029] (2) Breakthrough improvement in back bonding strength: Through the three-layer anchoring structure of "rough anchoring pit → sintered PTFE filling pit transition → secondary penetration of drip layer", the back peel strength can reach more than 12N / cm, which is far higher than the existing products of 5~8N / cm, and completely solves the problems of pressing wrinkling and delamination.
[0030] (3) Excellent thickness consistency: The sintered PTFE layer is only 5~10μm thick, the drip layer is completely penetrated into the micropores without additional thickness, and the overall thickness tolerance is controlled within ±0.02mm, which is suitable for high-precision high-frequency board pressing requirements.
[0031] (4) Strong process compatibility: The back sintering adopts short-time local heating, which does not affect the performance of the front PI. No additional heat insulation tooling is required, and it can be directly adapted to the existing production line. Attached Figure Description
[0032] Figure 1 This is a combined view of the various layers of the PCB buffer pad of the present invention; In the diagram: 1. PI layer; 2. Base fabric layer; 3. PTFE transition layer; 4. Composite backing layer. Detailed Implementation
[0033] The present application will now be further described in conjunction with the accompanying drawings and specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0034] In the description of this application, it should be understood that the terms "upper", "lower", "left", "right", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.
[0035] The terms "first," "second," etc., used in this application are used to distinguish similar objects and not to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that embodiments of this application can be implemented in orders other than those illustrated or described herein, and the objects distinguished by "first," "second," etc., are generally of the same class, not limited in number; for example, a first object can be one or more. Furthermore, in the specification and claims, "and / or" indicates at least one of the connected objects, and the character " / " generally indicates that the preceding and following objects are in an "or" relationship. Example 1:
[0036] like Figure 1 As shown, the PCB buffer pad is prepared by lamination using a horizontal coating machine. The stainless steel mirror panel surface used for lamination on the horizontal coating machine can be protected by adding a release layer to the steel plate, reducing the risk of adhesion. The release layer is preferably copper foil or PTFE machined film. During lamination, the PI layer 1 on the front side of the buffer pad forms surface contact with the steel plate side, without fixed connection, relying on pressure clamping and heating via the press's hot plate.
[0037] The invention will be further explained below with reference to a batch of industrial production data. The specific steps are as follows: 1. Base fabric preparation: Hongyan EW354 fiberglass cloth was selected as the base fabric layer 2. After dewaxing and fiber opening treatment, the weight was 354g / m² and the thickness was 0.37mm. 2. Coating of the front PI layer 1 (step S1): Mix 800g of oily polyimide emulsion with a solid content of 30% with 0.64g of 301 single-arm carbon nanotubes; coat twice on a horizontal coating machine with a feeding tension of 3±0.5Kg, a take-up tension of 4±0.5Kg, and a main speed of 4±0.5m / min. 3. Vertical dewaxing (step S2): Transfer to a vertical oven and increase the temperature in steps of 150℃ (6min) → 200℃ (6min) → 280℃ (6min) → 350℃ (6min). The coating surface should not be in contact with the top roller throughout the process. After dewaxing is completed, the coating layer is smooth and free of bubbles. 4. Reverse surface roughening (step S3): After roughening the surface of the base fabric with a 200# diamond roller, a micro-anchoring structure is formed; a uniform nap is formed on the reverse surface of the base fabric, and there are no breaks in the warp and weft yarns of the base fabric; 5. Reverse PTFE transition layer 3 scraping and sintering (step S4): PTFE emulsion with a solid content of 60% is scraped onto the roughened surface and dried at 350 degrees Celsius. The PTFE melts and fills more than 90% of the roughened anchoring pits to form a dense transition layer. The actual measured temperature on the front side does not exceed the upper limit of PI short-term temperature resistance.
[0038] 6. Reverse mixing emulsion dripping (step S5): A PTFE raw rubber + FEP mixture with a solid content of 20% is dripped onto the surface of the sintering transition layer and penetrates into the remaining micropores of the transition layer by capillary action; then it is dried in a 280℃ oven, the raw rubber forms a film but does not sinter, forming the composite back layer 4, and the final product has a total thickness of 0.36mm. Example 2:
[0039] Compared with Example 1, the difference is that the amount of 301 single-arm carbon nanotubes coated with the front PI layer is 0.48g. Example 3:
[0040] Compared with Example 1, the difference is that the amount of 301 single-arm carbon nanotubes coated with the front PI layer is 0.56g. Example 4:
[0041] Compared with Example 1, the difference is that the amount of 301 single-arm carbon nanotubes coated with the front PI layer is 0.72g. Example 5:
[0042] Compared with Example 1, the difference is that the amount of 301 single-arm carbon nanotubes coated with the front PI layer is 0.88g.
[0043] The applicant used the same batch of EW354 base fabric and the same process route, but with different amounts of 301 single-arm carbon nanotubes added. Tests were conducted on the PCB cushioning pads, and the test data are as follows: Table 1: Dispersed state (SEM observation) 3D network continuous density Discontinuous network, isolated and fragmented Network basic continuity Mild clustering in localized areas There was obvious aggregation, with micron-sized particles appearing. Thermal conductivity of the front side (W / (m·K)) 1.21 0.73 1.02 1.16 1.03 Dielectric constant Dk (@10GHz) 2.4 2.33 2.35 2.45 2.71 Dielectric loss Df (@10GHz) 0.0018 0.0015 0.0016 0.0022 0.0033 As shown in Table 1, the preferred addition amount of 301 single-arm carbon nanotubes is 0.07~0.09wt%, with the optimal value being 0.08wt%. Within this range: the lower limit of 0.07wt% indicates the critical point of the thermally conductive network, with a high risk of fluctuations in mass production; the core of 0.08wt% indicates a continuous, dense network without agglomeration, representing the peak of overall performance; and the upper limit of 0.09wt% indicates that the dielectric properties begin to deteriorate.
[0044] Table 2 shows the adhesion test results of commercially available kraft paper and PCM pads compared to Examples 1 / 3 / 4.
[0045] Table 2: Comparative Example A (kraft paper, commercially available) 1.6 16 25 Unable to count Comparative Example B (Regular PCM pad, commercially available) 7.5 175 226 11% Example 1 (0.07wt%) 11.8 480 473 (Mild) 0.6% Example 3 (0.08wt%) 12.1 ≥500 (Not found) ≥500 (Not found) 0% Example 4 (0.09wt%) 11.5 460 400 (Slight) 1.0% The above embodiments are merely preferred embodiments of this application and should not be construed as limiting the scope of protection of this application. Any non-substantial changes and substitutions made by those skilled in the art based on this application shall fall within the scope of protection claimed by this application.
Claims
1. A PCB cushioning pad, comprising a base fabric layer (2), a PI layer (1) and a PTFE transition layer (3) respectively disposed on the front and back sides of the base fabric layer (2), and a composite backing layer (4) disposed on the outside of the PTFE transition layer (3), characterized in that: The back of the base fabric layer (2) has a micro-anchoring structure. The PTFE transition layer (3) is filled in the micro-anchoring structure and anchored to the base fabric layer (2). The PI layer (1) is a polyimide layer containing thermally conductive filler. The composite back layer (4) is a mixed layer of PTFE raw rubber and FEP. The PI layer (1) on the front of the PCB buffer pad ensures low dielectric and wear resistance. The PTFE transition layer (3) and the composite back layer (4) on the back provide adhesion and cushioning. The micro-anchoring structure achieves mechanical interlocking between the PTFE transition layer (3) and the base fabric layer (2).
2. The PCB buffer pad according to claim 1, characterized in that: The thermally conductive filler is a single-arm carbon nanotube, and the amount added is 0.07~0.09% of the weight of the PI layer (1).
3. A PCB buffer pad according to claim 1, characterized in that: The composite back layer (4) is formed by curing a mixture of PTFE raw rubber and FEP, and the mass percentage of FEP in the composite back layer (4) is 15% to 25%.
4. A process for preparing a PCB buffer pad as described in any one of claims 1 to 3, characterized in that: The preparation process includes: S1, Front PI layer (1) coating: On a horizontal coating machine, a polyimide emulsion containing thermally conductive filler is scraped onto the front side of the dewaxed and fiber-opened base fabric. S2, Vertical Step Dewaxing: The coated base fabric is transferred into a vertical oven and dewaxed by stepping up the temperature from 150℃ to 200℃ to 280℃ to 350℃. Throughout the process, the coating surface is kept from sticking to the top roller to protect the carbon nanotube conductive network on the front side and ensure the dimensional stability of the base fabric. S3. Reverse treatment: The reverse side of the base fabric is roughened to form uniformly distributed micro-anchoring pits without cutting the warp and weft yarns of the base fabric. S4. PTFE coating and sintering on the reverse side: PTFE emulsion is coated on the reverse side of the base fabric after surface roughening treatment, followed by short-time high-temperature sintering at 350℃ to melt and fill the micro-anchoring pits. After cooling, a dense sintered PTFE transition layer is formed (3). Step S5, reverse side mixed emulsion dripping: The mixed emulsion of PTFE raw rubber and FEP is dripped onto the surface of the sintered PTFE transition layer (3). It penetrates into the remaining micropores of the transition layer by relying on capillary action and surface tension, so that the raw rubber forms a film but does not sinter. Then, it is dried at a low temperature of 280℃ to form a composite back side.
5. The PCB buffer pad manufacturing process according to claim 4, characterized in that: The emulsion in step S1 is an oily polyimide emulsion containing 0.07~0.09 wt% single-arm carbon nanotubes. The single-arm carbon nanotubes are type 301 single-arm carbon nanotubes, which are dispersed and added to the oily polyimide emulsion in two stages, with a total coating thickness of 25~35 μm.
6. The PCB buffer pad manufacturing process according to claim 4, characterized in that: In step S3, a 200# diamond roller is used to roughen the surface, with a roughening depth of 15~20μm and an anchoring pit density of ≥200 pits / mm².
7. The PCB buffer pad manufacturing process according to claim 4, characterized in that: The sintering temperature in step S4 is 350℃, the time is 6 minutes, and the front surface temperature is ≤350℃.
8. The PCB buffer pad manufacturing process according to claim 4, characterized in that: In step S4, sintering is a local back-side treatment. When the heat is conducted to the front side, it has dropped to below 350°C and does not affect the performance of the front PI layer (1).
9. The PCB buffer pad manufacturing process according to claim 4, characterized in that: The PTFE emulsion in step S4 has a solid content of 60%, a wet film thickness of 10-20 μm after coating, and a dry film thickness of 5-10 μm after sintering.
10. The PCB buffer pad manufacturing process according to claim 4, characterized in that: In step S5, the solid content of the PTFE raw rubber and FEP mixed emulsion is 18%~22%, the dripping amount is 20~40g / m², the drying temperature is 280℃, the raw rubber forms a film but does not sinter, and the thickness increase on the back side after lamination is ≤0.02mm.